Body composition and heart rate variability: relations to age, sex, obesity and physical activity - López Sánchez, G. F.; López Sánchez, L.; Díaz Suárez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
Body composition (BC) and heart rate variability (HRV) are closely related to the health of people. The two variables have been studied separately on numerous occasions, however, few studies have studied the whole relationship between the two concepts with, in many cases, conflicting results. The main objective of this paper is to review the scientific literature dealing with the relationship between BC and HRV from different points of view: in relation to age (children and adolescents, adults and seniors) in relation to obesity , sex and amount of physical activity. This review leads to the conclusion that there is a relationship between BC and HRV, so that decreased HRV is associated with a high percentage of body fat and a lower percentage of muscle mass.